Structure dependent dielectric response of spray coated nanostructured zirconia thin films. (22nd March 2019) - Mohan, Sreedevi R; Uma Maheswari, A; Sivakumar, M
Abstract: In this work the structural dependent dielectric property of ZrO2 nanoparticles and films prepared using these nanoparticles is studied. The tetragonal and monoclinic dominant zirconia nanoparticles were obtained through thermal treatment of PVP/CTAB capped hydrous amorphous zirconia (HAZ) at 500 °C. The grain (Rg ) and grain boundary (Rgb ) resistances of both types of nanoparticles along with films are estimated by fitting the respective complex impedance (Nyquist) plots with an equivalent electrical circuit. The nanostructured tetragonal dominant zirconia films are highly conductive as compared to monoclinic films due to large amount of Zr 3+ ions present at tetragonal sites. Consequently the film exhibits a high dielectric constant at lower frequency range due to Maxwell-Wagner polarization. Moreover the EPR signals observed at 1.946 (g∣∣ ) and 1.967 (g⊥ ) reveals the presence of greater Zr 3+ ions tetragonal films. The Rgb of monoclinic dominant film is increased by an order of 10 3 and consequently results in significant reduction of dielectric constant. Further the shift of loss tangent peak to higher frequency side of tetragonal dominant films endorses the higher mobility of charge carriers as that of monoclinic films. The enhancement of dielectric properties shows the potential application of tetragonal dominant ZrO2 films for future electronic devices.